High-strength hard alloy and preparation method and application thereof
By optimizing the formula and preparation process of cemented carbide, combined with wet ball milling and plasma activation treatment, the stability and preparation complexity of cemented carbide in high-temperature environments are solved, and high strength, toughness and high-temperature resistance are improved. Suitable for the manufacturing of high-temperature parts.
Patent Information
- Application Number
- CN202411677222.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing cemented carbides have shortcomings in high strength, toughness and heat resistance, especially in high temperature environments that are prone to cracks, deformation or failure, and the preparation process is complex, energy consumption is high, and the degree of densification is insufficient, which limits its application.
Using a high-strength cemented carbide formula, including tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and trace reinforcement elements (such as aluminum, boron or vanadium), through wet ball milling, plasma activation and Second-stage sintering and other processes form dense high-strength cemented carbide materials.
It significantly improves the toughness and high temperature resistance of the alloy, extends the service life, simplifies the production process, reduces energy consumption and production costs, and increases the density of the material, which is suitable for the manufacturing of high-temperature parts.
Smart Images

Figure CN119177387A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material science and technology, and in particular to a high-strength cemented carbide and a preparation method and application thereof. Background Art
[0002] Cemented carbide is a type of material with tungsten carbide as the main component combined with other metal elements such as cobalt and titanium. It is widely used in the manufacture of cutting tools, molds and wear-resistant parts due to its high hardness, high wear resistance and excellent heat resistance. However, with the continuous improvement of industrial requirements for material performance, the existing cemented carbide still has deficiencies in high strength, high toughness and heat resistance. Especially in high-temperature working environments, traditional cemented carbide materials are prone to cracks, deformation or failure, affecting service life and efficiency. In order to meet the needs of high-strength and long-life materials in modern industry, it is necessary to further improve the comprehensive performance of cemented carbide.
[0003] The existing cemented carbide formula has bottlenecks in balancing hardness and toughness. The improvement of hardness often leads to a decrease in toughness, and the high temperature resistance is also relatively limited. In addition, the traditional cemented carbide preparation process is complex, energy consumption is high, and the sintering densification degree is insufficient, resulting in uneven microstructure of the alloy material, thus limiting its application in high stress and high temperature environments. Therefore, an innovative alloy formula and optimized preparation method are urgently needed to solve the above problems. Summary of the invention
[0004] Based on the above objectives, the present invention provides a high-strength cemented carbide and a preparation method and application thereof.
[0005] A high-strength hard alloy, comprising tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and trace strengthening elements; wherein the mass percentage of each component is: Tungsten carbide accounts for 62.5%-84.7%; Cobalt accounts for 6%-12%; Tantalum carbide accounts for 3%-8%; Niobium carbide accounts for 2%-6%; Titanium carbide accounts for 3%-6%; Yttrium oxide accounts for 0.3%-1.5%; Nickel accounts for 0.5%-2%; Trace fortified elements account for 0.5%-2%; The trace strengthening element is aluminum, boron or vanadium.
[0006] A method for preparing high-strength cemented carbide comprises the following steps: S1: weighing raw materials of tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel, and trace strengthening elements according to preset weight percentages, and uniformly mixing the components to form a mixture A; S2: placing the mixture A in a wet ball milling device for ball milling to form a slurry; S3: drying the ball-milled slurry to obtain uniform dry powder; S4: performing plasma activation treatment on the dried powder to activate the surface of the powder particles; The S4 specifically includes: S41: The dry powder obtained in S3 is placed in a plasma activation device, and the vacuum degree in the device is controlled at to Pa; S42: setting the gas flow rate of the plasma, using argon or nitrogen as the working gas, and controlling the flow rate at 50-200 ml / min; S43: heating the powder to 400-600° C. for 30-60 minutes, and performing surface treatment by plasma to activate the surface of the powder particles; S44: After the treatment, the powder is cooled to room temperature; S5: pressing the activated powder to form a dense green body; S6: performing a two-stage sintering treatment on the green body in a vacuum sintering furnace; The S6 specifically includes: S61: Place the green body into a vacuum sintering furnace and set the vacuum degree to to Pa, start the first stage of sintering; S62: During the first sintering process, the temperature is raised to 800-1000°C for 1-2 hours to eliminate pores in the green body; S63: During the second sintering process, the temperature is further increased to 1450-1650°C and maintained for 2-4 hours to achieve complete bonding between particles; S7: After sintering is completed, cooling treatment is performed to finally obtain a high-strength cemented carbide material.
[0007] Optionally, the S2 specifically includes: S21: adding ethanol or deionized water to the mixture A as a medium for wet ball milling, wherein the amount of the medium added is 1 to 3 times the total weight of the mixture A; S22: placing the mixture A and the ball milling medium in a ball milling device, selecting the ball milling medium made of cemented carbide or zirconium oxide, and controlling the mass ratio of the ball milling medium to the raw material to be 5:1 to 10:1; S23: setting the ball milling speed to 200-400 rpm and the ball milling time to 10-20 hours; S24: After the ball milling is completed, filtering is performed to separate the ball milling medium to obtain a uniform slurry.
[0008] Optionally, the S3 specifically includes: S31: placing the slurry obtained in S2 in a spray drying device, and controlling the feed rate to 50-100 ml / min; S32: setting the air inlet temperature of the spray drying equipment to 150-250° C. and the air outlet temperature to 80-120° C. to spray dry the slurry; S33: After the drying process is completed, the dried powder is collected and sieving is performed to control the particle size to 1-5 microns to obtain a uniform dry powder.
[0009] Optionally, the S5 specifically includes: S51: placing the plasma activated powder into a die, wherein the die material is a carbide substrate, and the die size is selected according to the final shape of the green body; S52: applying pressure in a pressing device, the pressure being controlled at 150-250 MPa to gradually compact the powder to form a dense green body; S53: while maintaining the pressure, applying a preheating treatment from room temperature to 200° C., and maintaining the preheating time for 10-30 minutes; S54: After the pressing is completed, the green body is taken out and size trimmed.
[0010] Optionally, the S7 specifically includes: S71: After sintering is completed, the temperature in the sintering furnace is controlled at 1450-1650° C., and the temperature is slowly lowered at a rate of 10-20° C. / min until the temperature drops to 800° C.; S72: When the temperature drops to 800°C, the cooling rate is adjusted to 5-10°C / min, and the cooling is continued slowly until the temperature drops to 300°C; S73: After the temperature reaches 300° C., the heating is stopped and the mixture is naturally cooled to room temperature to complete the cooling process; S74: After cooling to room temperature, take out and obtain a high-strength cemented carbide material.
[0011] The above-mentioned high-strength cemented carbide and the above-mentioned method for preparing the high-strength cemented carbide are both used in the manufacture of cutting tools, molds, wear-resistant parts and high-temperature parts.
[0012] Beneficial effects of the present invention: The present invention optimizes the formula of high-strength cemented carbide and reasonably introduces tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and trace strengthening elements (such as aluminum, boron or vanadium). On the basis of ensuring high hardness, the toughness and high-temperature resistance of the alloy are significantly improved. By introducing innovative trace strengthening elements, the stability of the alloy in a high-temperature environment is improved, and the problems of material cracking and deformation under high temperature can be effectively dealt with, thereby extending the service life of the alloy.
[0013] The present invention simplifies the production process through innovative treatments such as plasma activation and two-stage sintering, while effectively improving the densification degree of the material. This process not only ensures the full combination of raw material particles and improves the microstructure of the material, but also reduces the energy consumption and production cost during the sintering process, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 A schematic diagram of each component of a high-strength cemented carbide according to an embodiment of the present invention; Figure 2 Schematic diagram of a method for preparing high-strength cemented carbide according to an embodiment of the present invention. DETAILED DESCRIPTION
[0016] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0017] It should be noted that the references to "one embodiment", "embodiment", "exemplary embodiments", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).
[0018] In general, a term can be understood, at least in part, from its use in context. For example, depending, at least in part, on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular sense, or can be used to describe a combination of features, structures, or characteristics in the plural sense. Additionally, the term "based on" can be understood as not necessarily intended to convey an exclusive set of factors, but can instead, depending, at least in part, on the context, allow for the presence of other factors that are not necessarily explicitly described.
[0019] Example 1 like Figure 1 As shown, a high-strength cemented carbide includes tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and trace strengthening elements; wherein the mass percentage of each component is, Tungsten carbide accounts for 72%; Cobalt accounts for 10%; Tantalum carbide accounts for 6%; Niobium carbide accounts for 4%; Titanium carbide accounts for 4%; Yttrium oxide accounts for 1%; Nickel accounts for 1.5%; Trace fortified elements account for 1.5%.
[0020] The trace strengthening element is aluminum.
[0021] like Figure 2 As shown, a method for preparing a high-strength cemented carbide comprises the following steps: S1: weighing raw materials of tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel, and trace strengthening elements according to preset weight percentages, and uniformly mixing the components to form a mixture A; S2: placing the mixture A in a wet ball mill for ball milling to form a slurry, thereby providing a suitable powder morphology for subsequent densification and sintering; S3: Drying the ball-milled slurry to obtain uniform dry powder, ensuring that the powder is easy to press and form in subsequent steps; S4: Plasma activation treatment is performed on the dried powder to activate the surface of the powder particles. The surface activity of the powder particles is enhanced through the surface energy excitation of the plasma, thereby promoting densification in the subsequent sintering process; S5: pressing the activated powder to form a dense green body; S6: performing a two-stage sintering process on the green body in a vacuum sintering furnace, wherein the first stage is used to eliminate internal pores, and the second stage is used to achieve densification of the green body; S7: After sintering is completed, cooling treatment is performed to finally obtain a high-strength cemented carbide material.
[0022] S2 specifically includes: S21: adding deionized water to the mixture A as a medium for wet ball milling, and the amount of the medium added is twice the total weight of the mixture A; S22: placing the mixture A and the ball milling medium in a ball milling device, selecting the ball milling medium made of cemented carbide, and controlling the mass ratio of the ball milling medium to the raw material to be 7:1; S23: setting the ball milling speed to 300 rpm and the ball milling time to 15 hours to ensure that the raw material particles are evenly mixed and refined; S24: After the ball milling is completed, filtering is performed to separate the ball milling medium to obtain a uniform slurry.
[0023] S3 specifically includes: S31: placing the slurry obtained in S2 in a spray drying device, and controlling the feed rate at 80 ml / min; S32: setting the air inlet temperature of the spray drying equipment to 200° C. and the air outlet temperature to 100° C. to spray dry the slurry; S33: After the drying process is completed, the dried powder is collected and sieving is performed to control the particle size to 3 microns to obtain a uniform dry powder.
[0024] S4 specifically includes: S41: The dry powder obtained in S3 is placed in a plasma activation device, and the vacuum degree in the device is controlled at Pa; S42: setting the gas flow rate of the plasma, using argon as the working gas, and controlling the flow rate at 100 ml / min; S43: heating the powder to 500° C., controlling the treatment time to 45 minutes, and performing surface treatment by plasma to activate the surface of the powder particles; S44: After the treatment, the powder is cooled to room temperature and used for the next step.
[0025] S5 specifically includes: S51: placing the plasma activated powder into a die, wherein the die material is a carbide substrate, and the die size is selected according to the final shape of the green body; S52: applying pressure in a pressing device, the pressure being controlled at 200 MPa, to gradually compact the powder to form a dense green body; S53: while maintaining the pressure, applying a preheating treatment from room temperature to 200° C., and maintaining the preheating time for 20 minutes to ensure close bonding between the powder particles; S54: After the pressing is completed, the green body is taken out and trimmed to ensure that the size and shape of the green body meet the requirements and is ready for the next step of sintering.
[0026] S6 specifically includes: S61: Place the green body into a vacuum sintering furnace and set the vacuum degree to Pa, start the first stage of sintering; S62: During the first sintering process, the temperature is raised to 900°C for 1.5 hours to eliminate pores in the green body and enhance the initial density of the material; S63: During the second sintering process, the temperature is further increased to 1550° C. and maintained for 3 hours to further densify the green body and achieve complete bonding between particles.
[0027] S7 specifically includes: S71: After sintering is completed, the temperature in the sintering furnace is controlled at 1550° C., and the temperature is slowly lowered at a rate of 15° C. / min until the temperature drops to 800° C.; S72: When the temperature drops to 800° C., the cooling rate is adjusted to 7° C. / min, and the cooling is continued slowly until the temperature drops to 300° C.; S73: After the temperature reaches 300° C., the heating is stopped and the mixture is naturally cooled to room temperature to complete the cooling process; S74: After cooling to room temperature, take out and obtain the high-strength cemented carbide material, and perform appearance inspection and size trimming to ensure that the alloy material meets the predetermined specification requirements.
[0028] The above-mentioned high-strength cemented carbide and the above-mentioned method for preparing the high-strength cemented carbide are both used in the manufacture of cutting tools, molds, wear-resistant parts and high-temperature parts.
[0029] Example 2 Material ratio: tungsten carbide 84.7%; cobalt 6%; tantalum carbide 3%; niobium carbide 2%; titanium carbide 3%; yttrium oxide 0.3%; nickel 0.5%; trace strengthening elements (boron): 0.5%.
[0030] The preparation steps are as follows: S1: Weigh tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and a trace amount of strengthening element aluminum according to the above ratio, and mix the components thoroughly to obtain a mixture A; S2: adding ethanol to the mixture A in an amount of 1 times the mass of the mixture A, using a ball milling medium made of zirconium oxide, with a mass ratio of the ball milling medium to the raw material of 5:1, and setting the ball milling speed to 200 rpm, the ball milling time to 10 hours, and after the ball milling is completed, filtering the slurry to obtain a uniform slurry; S3: feeding the slurry into the spray drying equipment at a feed rate of 50 ml / min, setting the inlet temperature to 150°C and the outlet temperature to 80°C for spray drying, and controlling the powder particle size after drying to 1 μm; S4: The dried powder is placed in a vacuum In Pa's plasma activation equipment, nitrogen was used as the working gas, the gas flow rate was controlled at 50 ml / min, the powder was heated to 400°C, the treatment time was 30 minutes, and after the treatment, the powder was cooled to room temperature; S5: placing the activated powder into a carbide substrate die, applying a pressure of 150 MPa, and preheating at room temperature for 10 minutes to press into a dense green body; S6: Place the green body in a vacuum state of The particles were sintered in a vacuum sintering furnace at 800°C for 1 hour in the first stage and 1450°C for 2 hours in the second stage to complete the bonding between particles. S7: After sintering, the temperature is lowered to 800°C at a rate of 10°C / min, and then further lowered to 300°C at a rate of 5°C / min, and finally naturally cooled to room temperature to obtain a high-strength cemented carbide material.
[0031] Example 3 Material ratio: tungsten carbide 62.5%; cobalt 12%; tantalum carbide 8%; niobium carbide 6%; titanium carbide 6%; yttrium oxide 1.5%; nickel 2%; trace strengthening elements (vanadium): 2%.
[0032] The preparation steps are as follows: S1: Weigh tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and a trace amount of strengthening element aluminum according to the above ratio, and mix the components thoroughly to obtain a mixture A; S2: deionized water is added to the mixture A in an amount of 3 times the mass of the mixture A, a ball milling medium made of cemented carbide is used, the mass ratio of the ball milling medium to the raw material is 10:1, and the ball milling speed is set to 400 rpm, and the ball milling time is 20 hours. After the ball milling is completed, the slurry is filtered to obtain a uniform slurry; S3: feeding the slurry into the spray drying equipment at a feed rate of 100 ml / min, setting the inlet temperature to 250°C and the outlet temperature to 120°C for spray drying, and controlling the particle size of the powder after drying to 5 μm; S4: The dried powder is placed in a vacuum In Pa's plasma activation equipment, argon was used as the working gas, the gas flow rate was controlled at 200 ml / min, the powder was heated to 600°C, the treatment time was 60 minutes, and after the treatment, the powder was cooled to room temperature; S5: placing the activated powder into a carbide substrate die, applying a pressure of 250 MPa, and preheating at room temperature for 30 minutes to press into a dense green body; S6: Place the green body in a vacuum state of The sintering was carried out in a vacuum sintering furnace of Pa; the first stage sintering temperature was 1000℃, and the temperature was kept for 2 hours; the second stage sintering temperature was 1650℃, and the temperature was kept for 4 hours to complete the bonding between particles; S7: After sintering, the temperature is lowered to 800°C at a rate of 20°C / min, and then further lowered to 300°C at a rate of 10°C / min, and finally naturally cooled to room temperature to obtain a high-strength cemented carbide material.
[0033] Table 1 Performance comparison of high strength cemented carbide finished products The following conclusions can be drawn from the comparison of the above Table 1: the hardness of Example 1 is the highest, reaching 2100 HV, which is better than the other two examples, showing that the alloy has a strong deformation resistance; the bending strength of Example 1 is the highest, reaching 3200MPa, indicating that the alloy performs well under bending load; the density of Example 2 is the highest, although the high density may affect other physical properties such as toughness and processability; the compressive strength of Example 1 is the highest, showing excellent bearing capacity under compression load; the wear rate of Example 1 is the lowest, indicating that it has the best wear resistance and is suitable for use in high wear environments; the toughness of Example 1 is the highest, combining an excellent balance of hardness and impact resistance; the sintering shrinkage of Example 1 is the lowest, showing a high dimensional stability. Based on the above data, Example 1 performs best in multiple aspects such as hardness, bending strength, compressive strength, wear resistance and toughness, and has the best comprehensive performance.
[0034] Table 2 Comparison of other performances As can be seen from Table 2 above, the thermal conductivity of Example 1 is 80 W / m·K, which shows its high thermal conductivity and is suitable for the heat dissipation requirements of high temperature environments; the thermal expansion coefficient of Example 1 is low, which is 5.2, indicating that the dimensional stability of the alloy is stronger when the temperature changes; the corrosion rate of Example 1 is the lowest, which is only 0.02%, showing very excellent corrosion resistance; the high temperature oxidation stability of Example 1 is the best, and the oxidation rate at high temperature is only 0.15%, which can maintain good chemical stability at high temperatures; the impact resistance of Example 1 is 2.5 MJ / m², which is superior to other embodiments and has better impact absorption capacity; the fracture toughness of Example 1 is the highest, which is 10 MPa·m^0.5, showing good fracture resistance; the processing performance of Example 1 is the best, and the cutting speed can reach 200 m / min, which means that the alloy is more efficient during processing. In summary, Example 1 has obvious advantages in thermal conductivity, corrosion resistance, oxidation stability, impact resistance, fracture toughness and processing, so it can be determined as the best embodiment.
[0035] The present invention covers any substitution, modification, equivalent method and scheme made on the essence and scope of the present invention. In order to make the public have a thorough understanding of the present invention, specific details are described in detail in the following preferred embodiments of the present invention, but those skilled in the art can fully understand the present invention without the description of these details. In addition, in order to avoid unnecessary confusion about the essence of the present invention, well-known methods, processes, procedures, components and circuits are not described in detail.
[0036] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength cemented carbide, characterized in that: It includes tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel and trace strengthening elements; the mass percentage of each component is: Tungsten carbide accounts for 62.5%-84.7%; Cobalt accounts for 6%-12%; Tantalum carbide accounts for 3%-8%; Niobium carbide accounts for 2%-6%; Titanium carbide accounts for 3%-6%; Yttrium oxide accounts for 0.3%-1.5%; Nickel accounts for 0.5%-2%; Trace fortified elements account for 0.5%-2%; The trace strengthening element is aluminum, boron or vanadium.
2. A method for preparing the high-strength cemented carbide according to claim 1, characterized in that: The following steps are involved: S1: weighing raw materials of tungsten carbide, cobalt, tantalum carbide, niobium carbide, titanium carbide, yttrium oxide, nickel, and trace strengthening elements according to preset weight percentages, and uniformly mixing the components to form a mixture A; S2: placing the mixture A in a wet ball milling device for ball milling to form a slurry; S3: drying the ball-milled slurry to obtain uniform dry powder; S4: performing plasma activation treatment on the dried powder to activate the surface of the powder particles; The S4 specifically includes: S41: The dry powder obtained in S3 is placed in a plasma activation device, and the vacuum degree in the device is controlled at to Pa; S42: setting the gas flow rate of the plasma, using argon or nitrogen as the working gas, and controlling the flow rate at 50-200 ml / min; S43: heating the powder to 400-600° C. for 30-60 minutes, and performing surface treatment by plasma to activate the surface of the powder particles; S44: After the treatment, the powder is cooled to room temperature; S5: pressing the activated powder to form a dense green body; S6: performing a two-stage sintering process on the green body in a vacuum sintering furnace; The S6 specifically includes: S61: Place the green body into a vacuum sintering furnace and set the vacuum degree to to Pa, start the first stage of sintering; S62: During the first sintering process, the temperature is raised to 800-1000°C for 1-2 hours to eliminate pores in the green body; S63: During the second sintering process, the temperature is further increased to 1450-1650°C and maintained for 2-4 hours to achieve complete bonding between particles; S7: After sintering is completed, cooling treatment is performed to finally obtain a high-strength cemented carbide material.
3. The method for preparing a high-strength cemented carbide according to claim 2, characterized in that: The S2 specifically includes: S21: adding ethanol or deionized water to the mixture A as a medium for wet ball milling, wherein the amount of the medium added is 1 to 3 times the total weight of the mixture A; S22: placing the mixture A and the ball milling medium in a ball milling device, selecting the ball milling medium made of cemented carbide or zirconium oxide, and controlling the mass ratio of the ball milling medium to the raw material to be 5:1 to 10:1; S23: setting the ball milling speed to 200-400 rpm and the ball milling time to 10-20 hours; S24: After the ball milling is completed, filtering is performed to separate the ball milling medium to obtain a uniform slurry.
4. The method for preparing a high-strength cemented carbide according to claim 2, characterized in that: The S3 specifically includes: S31: placing the slurry obtained in S2 in a spray drying device, and controlling the feed rate at 50-100 ml / min; S32: setting the air inlet temperature of the spray drying equipment to 150-250° C. and the air outlet temperature to 80-120° C. to spray dry the slurry; S33: After the drying process is completed, the dried powder is collected and sieving is performed to control the particle size to 1-5 microns to obtain a uniform dry powder.
5. The method for preparing a high-strength cemented carbide according to claim 2, characterized in that: The S5 specifically includes: S51: placing the plasma activated powder into a die, wherein the die material is a carbide substrate, and the die size is selected according to the final shape of the green body; S52: applying pressure in a pressing device, the pressure being controlled at 150-250 MPa to gradually compact the powder to form a dense green body; S53: while maintaining the pressure, applying a preheating treatment from room temperature to 200° C., and maintaining the preheating time for 10-30 minutes; S54: After the pressing is completed, the green body is taken out and size trimmed.
6. The method for preparing a high-strength cemented carbide according to claim 2, characterized in that: The S7 specifically includes: S71: After sintering is completed, the temperature in the sintering furnace is controlled at 1450-1650° C., and the temperature is slowly lowered at a rate of 10-20° C. / min until the temperature drops to 800° C.; S72: When the temperature drops to 800°C, the cooling rate is adjusted to 5-10°C / min, and the cooling is continued slowly until the temperature drops to 300°C; S73: After the temperature reaches 300° C., the heating is stopped and the mixture is naturally cooled to room temperature to complete the cooling process; S74: After cooling to room temperature, take out and obtain a high-strength cemented carbide material.
7. The high-strength cemented carbide according to claim 1 is used in the manufacture of cutting tools, molds, wear-resistant parts and high-temperature parts.
Citation Information
Patent Citations
Method for manufacturing hard alloy numerical control blade
CN102019424A
High strength alloy cutter head and preparation method thereof
CN105154745A
Preparation method of high-wear-resistance WC-based hard alloy
CN110735075A
Multi-scale hard alloy friction stir welding stirring head and preparation method thereof
CN117867355A
Gradient hard alloy and preparation method thereof
CN118621169A
Cited By
Miniature deep groove ball bearing for fishing reel and preparation method of miniature deep groove ball bearing
CN120679992A
Stainless steel part and hot isostatic pressing preparation method and application thereof
CN120715217A
Powder metallurgy near-net forming method for high-purity iron TD4 thin-wall complex component
CN121467702A
Long-life type superfine low-cobalt hard alloy cutter, formula and preparation method
CN122542901A
